Comprehensive Review on Routing Protocols for Wireless Body Area Networks - Swati Goel; Kalpna Guleria; Surya Narayan Panda (International Journal of Mathematical, Engineering and Management Sciences)
In today's era, the deployment of wearable and implantable devices and sensor nodes is expanding, giving rise to new research directions in Wireless Body Area Networks (WBANs) to address the various challenges such as efficient routing, security, interoperability, power consumption, energy optimization, fault-tolerance, reliable communication, etc. Among all the challenges, routing is one of the most important factors that needs consideration for data transmission. With the use of wearable (on-body) or implanted (in-body) sensors, WBANs are utilized in e-healthcare systems to retrieve physiological parameters from the human body, and systematically route them to a remote server. High network performance and effective communication depend on the routing protocol's design. Consequently, the primary objective of this work is to provide a comprehensive taxonomy of the most advanced routing protocols used in WBANs. This review paper discusses the different WBAN routing protocols from recent years, reported from 2019 to 2024. The different categories related to WBAN routing are addressed while highlighting their objectives, problem specifications, advantages, disadvantages, simulation tools, and performance metrics. These routing protocols are evaluated and compared in terms of performance parameters like energy, congestion control, data priority, scalability, latency, Packet Delivery Ratio (PDR), node temperature, network lifetime, throughput, security, path loss, etc. Finally, the research gaps are summarized from the reviewed protocols, and future research aspects are discussed.